The (dis-)connection between selection research in sports and business literature – a citation network analysis - Brinkmöller, Birte; Dreiskämper, Dennis; Höner, Oliver; Strauss, Bernd (Frontiers in Psychology, 2025)
Sports associations and companies share a common goal of identifying and selecting top talent, prompting a growing interest in refining their selection processes. Recent decades have witnessed increased attention to predictive valid constructs (e.g., motivation) and predictive assessment methods (e.g., questionnaires). Leveraging an extensive history and empirical evidence from personnel selection research in business, a cross-contextual knowledge transfer could offer potential benefits for both sports and business. To examine the utilization of information between sports and the business context, this study explores the connection between these contexts. Analyzing 20,492 articles from SCOPUS and Web of Science databases, we followed PRISMA guidelines and conducted a citation network analysis (n = 940 articles). Results reveal limited interconnectivity (3,728 links), with only six articles cited between contexts: three sports articles cited business articles and vice versa. Sports articles referred to business research for talent definition, skill assessment, and methodological concerns. Contrarily, the business domain primarily used sports research as examples and for individual aspects of talent development models. This study highlights the potential for points of connection, including requirement analysis, skill assessment, and research on predictive validity. Future research should systematically explore shared and underrepresented topics in both contexts, such as the use of, for example, situational judgement tests in sports to enhance talent selection in sports, drawing insights from the business domain.Systematic review registrationhttps://aspredicted.org/366x-7cfd.pdf.